Answer:
2874.33 m/s²
Step-by-step explanation:
t = Time taken
u = Initial velocity
v = Final velocity
s = Displacement
a = Acceleration
g = Acceleration due to gravity = 9.81 m/s²
![v^2-u^2=2as\\\Rightarrow a=(v^2-u^2)/(2s)\\\Rightarrow a=(v^2-0^2)/(2* h)\\\Rightarrow v^2=2ah\ m/s](https://img.qammunity.org/2020/formulas/physics/college/2i9go7tg572e3ujkuafegxdxux6jbceci9.png)
Now H-h = 0.588 - 0.002 = 0.586 m
The final velocity will be the initial velocity
![v^2-u^2=2as\\\Rightarrow 0^2-u^2=2gs\\\Rightarrow -2ah=2* g(H-h)\\\Rightarrow -2a0.002=2* g0.586\\\Rightarrow a=-(0.586* -9.81)/(0.002)\\\Rightarrow a=2874.33\ m/s^2](https://img.qammunity.org/2020/formulas/physics/college/6g20vsppn8i7ovto3curc4nzzqzbmczhz4.png)
Acceleration of the frog is 2874.33 m/s²